2000
DOI: 10.1016/s0014-5793(00)01843-3
|View full text |Cite
|
Sign up to set email alerts
|

The initial pathogenesis of cadmium induced renal toxicity

Abstract: The novel application of magic angle spinning 1 H NMR spectroscopy, coupled with pattern recognition techniques, has identified biochemical changes in lipid and glutamate metabolism that precede classical nephrotoxicity. These changes occurred in the bank vole (Clethrionomys glareolus) after chronic dosing, at a low level of exposure and at a renal Cd 2+ concentration (8.4 W Wg/g dry wt) that was nearly two orders of magnitude below the WHO critical organ concentration (200 W Wg/g wet wt). These early stage ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…These studies have allowed the identification of some metabolites (acetilspermidine, glucose, histidine, l-methylhistidine, mannose) that can be used as biomarkers for Cu, Cd and Zn pollution in various animal species (Bundy et al 2004(Bundy et al , 2008Taylor et al 2009;Guo et al 2009). In rats, in addition to the changes in amino acid and sugar contents, a further abnormal metabolome composition has been observed as a result of Cd and Cu intake (Jones et al 2007;Lei et al 2008), and changes in lipid metabolism under high levels of As have also been observed (Griffin et al 2000). A tendency to increase the production of AMP, ADP and N-a-methylhistidine, and to generate an imbalance in metabolites related to energetics by reducing ATP levels has been reported in Lumbricus rubellus (Bundy et al , 2008.…”
Section: Hypoxiamentioning
confidence: 98%
See 1 more Smart Citation
“…These studies have allowed the identification of some metabolites (acetilspermidine, glucose, histidine, l-methylhistidine, mannose) that can be used as biomarkers for Cu, Cd and Zn pollution in various animal species (Bundy et al 2004(Bundy et al , 2008Taylor et al 2009;Guo et al 2009). In rats, in addition to the changes in amino acid and sugar contents, a further abnormal metabolome composition has been observed as a result of Cd and Cu intake (Jones et al 2007;Lei et al 2008), and changes in lipid metabolism under high levels of As have also been observed (Griffin et al 2000). A tendency to increase the production of AMP, ADP and N-a-methylhistidine, and to generate an imbalance in metabolites related to energetics by reducing ATP levels has been reported in Lumbricus rubellus (Bundy et al , 2008.…”
Section: Hypoxiamentioning
confidence: 98%
“…Thus, if the aims are also to determine possible novel structures, the use of 1 HNMR is advisable. A set of recent partial ecometabolomic studies of polar metabolites has also permitted the identification of the metabolites and metabolic pathways affected by certain trace element polluting plants (Bailey et al 2003;Roessner et al 2006;Sarry et al 2006;Le Lay et al 2006;Sun et al 2008) and animals (Gibbs et al 1997;Griffin et al 2001Griffin et al , 2000Bundy et al 2007Bundy et al , 2004Jones et al 2008b;Taylor et al 2009;Guo et al 2009) (Table 2). These studies have allowed the identification of some metabolites (acetilspermidine, glucose, histidine, l-methylhistidine, mannose) that can be used as biomarkers for Cu, Cd and Zn pollution in various animal species (Bundy et al 2004(Bundy et al , 2008Taylor et al 2009;Guo et al 2009).…”
Section: Hypoxiamentioning
confidence: 99%
“…This approach allows rapid analysis of the biofluid profiles of samples taking advantage of the degree of inherent biochemical similarities between samples and has been used as a powerful tool in metabonomic studies in the fields of drug toxicology and disease diagnosis (11)(12)(13)(14). NMR-based metabonomics provides an insight into the site, severity, and mechanisms of toxic damage (15)(16)(17) when applied in biofluids and tissues from animals treated with drugs and toxins, and allows simultaneous monitoring of a variety of endogenous metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that an elevation of acetate was not observed in HgCl 2 treated kidney samples would imply that HgCl 2 may instead cause acidosis in the kidney. HgCl 2 -induced acidosis has been described previously in HgCl 2 -and cadmium-treated rats [14,22].…”
Section: Assessment Of the Metabolic Effects Of Hgcl 2 On The Renal Cmentioning
confidence: 90%
“…1 H HRMAS NMR spectroscopy has been successfully applied to study many types of tissue including liver [5,10], kidney [11] and testis [7] in rats, and a range of human tissues from healthy and diseased populations [12,13]. 1 H HRMAS approaches have also been applied to a few toxin studies in experimental animals with toxins including arsenic (As 3+ ) [8], cadmium [14,15] 2-bromoethanamine [6] and thioacetamide [16]. HgCl 2 is a potent and well-known model for induction of renal cortical toxicity and targets the S2/S3 portion of the renal proximal tubules of experimental animals [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%